2015
DOI: 10.1044/2015_jslhr-l-15-0056
|View full text |Cite
|
Sign up to set email alerts
|

A Read-Aloud Storybook Selection System for Prereaders at the Preschool Language Level: A Pilot Study

Abstract: This empirically derived difficulty-level system created for storybooks read aloud to preschoolers represents a step toward filling a gap in the read-aloud literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Books that were complex along one dimension (more theory of mind, more words per page, more advanced story structure, greater distance from the child's own experience) were likely to be complex along all of the other dimensions. This result is consistent with the results in Schwarz et al (2015) who similarly found that various dimensions of complexity (linguistic, inferencing, story structure, familiarity of the situations for the child) were predictive of whether experts (speech language pathologists) would classify the book as “easy” or “difficult.” The current results further supported the idea that all the features that contribute to complexity work together coherently across a wide variety of books.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Books that were complex along one dimension (more theory of mind, more words per page, more advanced story structure, greater distance from the child's own experience) were likely to be complex along all of the other dimensions. This result is consistent with the results in Schwarz et al (2015) who similarly found that various dimensions of complexity (linguistic, inferencing, story structure, familiarity of the situations for the child) were predictive of whether experts (speech language pathologists) would classify the book as “easy” or “difficult.” The current results further supported the idea that all the features that contribute to complexity work together coherently across a wide variety of books.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, more traditional stories were less likely to closely reflect the child's own life. This clustering of features corresponds roughly to the features in Schwarz et al (2015) that led speech language pathologists to classify a book as being comparatively “easy” (shorter sentences, less complex story structure, fewer abstract concepts, and greater similarity to the child's own experience) vs. “hard” (greater complexity in the story structure and language as well as more distance from the child's experience).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations